Sepsis inhibits tumor growth in mice with cancer through Toll-like receptor 4-associated enhanced Natural Killer cell activity. (2nd November 2019) - Vigneron, Clara; Mirouse, Adrien; Merdji, Hamid; Rousseau, Christophe; Cousin, Clément; Alby-Laurent, Fanny; Mira, Jean-Paul; Chiche, Jean-Daniel; Llitjos, Jean-François; Pène, Frédéric
ABSTRACT: Sepsis-induced immune dysfunctions are likely to impact on malignant tumor growth. Sequential sepsis-then-cancer models of tumor transplantation in mice recovering from sepsis have shown that the post-septic immunosuppressive environment was able to promote tumor growth. We herein addressed the impact of sepsis on pre-established malignancy in a reverse cancer-then sepsis experimental model. Mice previously inoculated with MCA205 fibrosarcoma cells were subjected to septic challenges by polymicrobial peritonitis induced by cecal ligation and puncture or endotoxinic shock. The anti-tumoral immune response was assessed through the distribution of tumor-infiltrating immune cells, as well as the functions of cytotoxic cells. As compared to sham surgery, polymicrobial sepsis dampened malignant tumor growth in wild-type (WT) mice, but neither in Toll-like receptor 4 ( Tlr4) −/- nor in Myd88 −/- mice. Similar tumor growth inhibition was observed following a LPS challenge in WT mice, suggesting a regulatory role of Tlr4 in this setting. The low expression of MHC class 1 onto MCA205 cells suggested the involvement of Natural Killer (NK) cells in sepsis-induced tumor inhibition. Septic insults applied to mice with cancer promoted the main anti-tumoral NK functions of IFNγ production and degranulation. The anti-tumoral properties of NK cells obtained from septic mice were exacerbated when cultured with MHC1 low MCA205 or YAC-1 cells. These results suggest that sepsis may harbor dual effects on tumor growth depending on the sequential experimental model. When applied in mice with cancer, sepsis prevents tumor growth in a Tlr4-dependent manner by enhancing the anti-tumoral functions of NK cells.